URU International Conference on Science and Technology 2016 - Ruangdet Wongla (Trans Tech Publications Ltd, 2017)
Selected, peer reviewed papers from the Uttaradit Rajabhat University International Conference on Science and Technology 2016 (URU ICST 2016), August 1-2, 2016, Uttaradit, Thailand